2021
DOI: 10.1111/jpn.13507
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of traditional Chinese medicine prescription and rumen‐protected γ‐aminobutyric acid on beef cattle under heat stress

Abstract: Heat stress (HS), which is usually induced by both hot and humid weather, inhibits animal productivity (Bloemhof et al., 2013).When the animals are under HS, the growth rate is affected by various adverse factors, such as feed intake reduction, rumen environment disturbance and nutrient digestibility descent (Berman, 2005). Numerous studies have proposed that HS increases the animal breeding cost and economic losses to the livestock industry due to the decrease in feed intake and nutrient digestibility (Chand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…GABA mainly exerts effects by binding to GABRP, which played an important role during the process of embryo implantation and placenta formation [ 14 , 39 , 40 ]. Previous studies have confirmed that GABRP is widely distributed in various tissues of sows during late gestation [ 15 ], and GABRP expression was significantly increased during the embryo implantation in human and mice [ 39 , 40 ], which suggested that GABRP may be important for embryo development and mother–fetus communication. Our results found that oxidative stress significantly down-regulated the expression of the GABRP gene in pTr-2 cells, while GABA pretreatment can increase the expression of the GABRP gene, indicating that GABA may exert an anti-oxidative effect by combining with GABRP.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…GABA mainly exerts effects by binding to GABRP, which played an important role during the process of embryo implantation and placenta formation [ 14 , 39 , 40 ]. Previous studies have confirmed that GABRP is widely distributed in various tissues of sows during late gestation [ 15 ], and GABRP expression was significantly increased during the embryo implantation in human and mice [ 39 , 40 ], which suggested that GABRP may be important for embryo development and mother–fetus communication. Our results found that oxidative stress significantly down-regulated the expression of the GABRP gene in pTr-2 cells, while GABA pretreatment can increase the expression of the GABRP gene, indicating that GABA may exert an anti-oxidative effect by combining with GABRP.…”
Section: Discussionmentioning
confidence: 86%
“…Gamma-aminobutyric acid (GABA) is a natural important functional nonessential amino acid that has several physiological functions, such as anti-inflammation, anti-apoptosis, and anti-oxidation [ 11 , 12 , 13 , 14 ]. Although GABA is an inhibitory neurotransmitter in the mammalian central nervous system, GABA signals also widely exist in peripheral tissues and organs, such as the ovaries, placenta, and uterus [ 15 , 16 , 17 ]. At the same time, early studies have shown that GABA can activate the GABA receptor π subunit (GABRP) to regulate the development of human chorionic trophoblast cells [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higher DMI and stable lactation in dairy cows require a better antioxidant status, which is reflected by changes in serum metabolites ( 12 , 34 ). SOD plays an important role in the animal’s antioxidant defense mechanism, while GSH-PX scavenges peroxides and hydroxyl radicals produced during cellular respiratory metabolism ( 19 , 35 ). T-AOC is the total antioxidant level of various antioxidants and antioxidant enzymes, representing the body’s ability to fight oxidation ( 12 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, dietary supplementation with GABA improved nutrient digestibility, growth performance and antioxidant status in heat-stressed beef cows ( 18 ). Chen et al study showed that GABA in synergy with Chinese herbs could effectively modulate the heat stress response in beef cows by improving antioxidant capacity, serum parameters and heat shock protein (HSP) expression ( 19 ). Previous studies have shown GABA to be beneficial to heat-stressed cows in terms of feed intake, lactation performance and animal health.…”
Section: Introductionmentioning
confidence: 99%
“…Рецепты традиционной китайской медицины (ТКМ) или ГАМК, защищённые от рубца (RP-GABA), могут эффективно облегчить тепловой стресс (HS) у крупного рогатого скота, но совместное влияние лекарственных растений и защита их от рубцового пищеварения на стресс у крупного рогатого скота полностью не выяснено. В результате проведённого исследования Jian Chen и соавторами было выявлено, ТКМ или ГАМК могут эффективно смягчать реакцию ГС у мясного скота за счет улучшения антиоксидантной способности, параметров сыворотки и экспрессии, в то время как их комбинация оказывает синергетический эффект на облегчение ГС (Chen J et al, 2021).…”
Section: лекарственное растение шлемник байкальский (Scutellaria Baic...unclassified